2016
DOI: 10.1155/2016/6829283
|View full text |Cite
|
Sign up to set email alerts
|

The Pathophysiological Impact of HLA Class Ia and HLA-G Expression and Regulatory T Cells in Malignant Melanoma: A Review

Abstract: Malignant melanoma, a very common type of cancer, is a rapidly growing cancer of the skin with an increase in incidence among the Caucasian population. The disease is seen through all age groups and is very common in the younger age groups. Several studies have examined the risk factors and pathophysiological mechanisms of malignant melanoma, which have enlightened our understanding of the development of the disease, but we have still to fully understand the complex immunological interactions. The examination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 110 publications
0
10
0
2
Order By: Relevance
“…Human leukocyte antigens (HLA) play crucial roles in the interaction of malignant cells with immune cells. 15 Various studies have shown that SOCS1 regulates MHC I and II molecules levels in fibroblast and tumor cells. [16][17][18] In pre-treatment tumors collected from patients with UM treated with immunotherapy, R expressed higher SOCS1, HLA-DRB4, and HLA-G than NR (figure 5C).…”
Section: Socs1 As a Potential Mediator In Um Responding To Immunotherapymentioning
confidence: 99%
“…Human leukocyte antigens (HLA) play crucial roles in the interaction of malignant cells with immune cells. 15 Various studies have shown that SOCS1 regulates MHC I and II molecules levels in fibroblast and tumor cells. [16][17][18] In pre-treatment tumors collected from patients with UM treated with immunotherapy, R expressed higher SOCS1, HLA-DRB4, and HLA-G than NR (figure 5C).…”
Section: Socs1 As a Potential Mediator In Um Responding To Immunotherapymentioning
confidence: 99%
“…The role of HLA class I molecules has been implied in tumor resistance to apoptosis (Sabapathy and Nam, 2008). Recent findings suggest that the altered expression of HLA molecules is associated with metastatic progression and poor prognosis in the tumor (Aptsiauri et al, 2007;Mendez et al, 2009;Johansen et al, 2016). The modification of surface molecules, lack of co-stimulatory molecules, production of immunosuppressive cytokines, and alterations in HLA molecules are some of the primary escape mechanisms used by tumor cells to evade the immune response (Garrido et al, 2010), which can directly distress the survival of an individual.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have implied that specific HLA‐G haplotypes may be associated with fertility and pregnancy complications such as reduced success in relation to in vitro fertilization treatments and recurrent spontaneous abortions . Furthermore, HLA‐G gene polymorphism may also be associated with the prognosis of certain types of cancers, as some studies have shown HLA‐G to be expressed by tumor cells . The HLA‐G genotype might also be important in relation to the prognosis of organ transplants according to some studies .…”
Section: Discussionmentioning
confidence: 99%
“…1,21 Furthermore, HLA-G gene polymorphism may also be associated with the prognosis of certain types of cancers, as some studies have shown HLA-G to be expressed by tumor cells. [22][23][24] The HLA-G genotype might also be important in relation to the prognosis of organ transplants according to some studies. [25][26][27] For the current study, we have used in silico phasing to obtain the haplotypes, which is an easy, inexpensive and reliable method to determine haplotypes and diplotypes in polymorphic genes.…”
Section: Promo-g0104amentioning
confidence: 99%